Calcium isotopes support spatial redox gradients on the Tethys European margin across the Triassic-Jurassic boundary - Ashley N. Prow-Fleischer; Zunli Lu; Clara L. Blättler; Tianchen He; Pulkit Singh; Preston Cosslett Kemeny; Jordan P. Todes; Alexandre Pohl; Tripti Bhattacharya; Bas van de Schootbrugge; Paul B. Wignall; Simona Todaro; et al. (Chemical Geology, 2025)

A new type of submarine chimneys built of halite - C. Siebert; D. Ionescu; U. Mallast; S. Merchel; B. Merkel; P. Möller; S. Pavetich; T. Pohl; T. Rödiger; Y. Yechieli (Science of The Total Environment, 2024)

The mediating role of cortical thickness and gray matter volume on sleep slow-wave activity during adolescence - Aimée Goldstone; Adrian R. Willoughby; Massimiliano de Zambotti; Peter L. Franzen; Dongjin Kwon; Kilian M. Pohl; Adolf Pfefferbaum; Edith V. Sullivan; Eva M. Müller-Oehring; Devin E. Prouty; Brant P. Hasler; Duncan B. Clark; et al. (Brain Structure and Function, 2018)

Structural brain anomalies in healthy adolescents in the NCANDA cohort: relation to neuropsychological test performance, sex, and ethnicity - Edith V. Sullivan; Barton Lane; Dongjin Kwon; M. J. Meloy; Susan F. Tapert; Sandra A. Brown; Ian M. Colrain; Fiona C. Baker; Michael D. De Bellis; Duncan B. Clark; Bonnie J. Nagel; Kilian M. Pohl; et al. (Brain Imaging and Behavior, 2017)

Neuroinformatics Software Applications Supporting Electronic Data Capture, Management, and Sharing for the Neuroimaging Community - B. Nolan Nichols; Kilian M. Pohl (Neuropsychology Review, 2015)

Global low-frequency motions in protein allostery: CAP as a model system - Philip D. Townsend; Thomas L. Rodgers; Ehmke Pohl; Mark R. Wilson; Tom C. B. McLeish; Martin J. Cann (Biophysical Reviews, 2015)

Safety and Biocompatibility of Carbohydrate-Functionalized Polyanhydride Nanoparticles - Julia E. Vela-Ramirez; Jonathan T. Goodman; Paola M. Boggiatto; Rajarshi Roychoudhury; Nicola L. B. Pohl; Jesse M. Hostetter; Michael J. Wannemuehler; Balaji Narasimhan (The AAPS Journal, 2015)

Temperature changes in the mid‐ and high‐ latitudes of the Southern Hemisphere - Y. Richard; M. Rouault; B. Pohl; J. Crétat; I. Duclot; S. Taboulot; C. J. C. Reason; C. Macron; D. Buiron (International Journal of Climatology, 2013)
A Hierarchical Ascending Classification is used to regionalize monthly temperature anomalies measured at 24 weather stations in Antarctica and the Sub‐Antarctic and mid‐latitude southern islands from 1973 to 2002. Three principal regions are identified that are geographically coherent: Eastern Antarctica, the Antarctic Peninsula and the Sub‐Antarctic and mid‐latitude islands. Within each region, consistent trends are observed: namely, stationary temperatures in ‘East‐Antarctica’; a robust warming in the ‘Sub‐Antarctic and mid‐latitude islands’, most pronounced in austral summer (nearly 0.5 °C per decade); and a strong but more recent warming in the ‘Antarctic Peninsula’. Austral summer temperature anomalies are related to (1) the Southern Annular Mode (SAM) indexes computed using two reanalysis products (20th Century Reanalyses and ERA40) over two periods (1958–2002 and 1973–2002), (2) the seasonal frequencies of four recurrent daily weather regimes identified with a k ‐means algorithm applied on the 500hPa geopotential height (DJF 1958–2002) and (3) HadSST2 sea surface temperature (SST) anomalies (DJF 1958–2002). East‐Antarctica interannual temperature anomalies are associated with the SAM variability. In the Antarctic Peninsula, only the long‐term trend is common with the SAM. The SAM does impact significantly the temperature anomalies of the Sub‐Antarctic and mid‐latitude islands. Trend and interannual variability of the islands' temperatures are associated with the nearby SST. For the Indian Ocean stations, warming in the Agulhas Current system could also have led to these changes. Copyright © 2012 Royal Meteorological Society

Tropical-temperate interactions over southern Africa simulated by a regional climate model - N. Vigaud; B. Pohl; J. Crétat (Climate Dynamics, 2012)

Magnetic Stents Retain Nanoparticle-Bound Antirestenotic Drugs Transported by Lipid Microbubbles - T. Räthel; H. Mannell; J. Pircher; B. Gleich; U. Pohl; F. Krötz (Pharmaceutical Research, 2012)

Coastal oceanic climate change and variability from 1982 to 2009 around South Africa - M Rouault; B Pohl; P Penven (African Journal of Marine Science, 2010)

Interactions between synoptic, intraseasonal and interannual convective variability over Southern Africa - B. Pohl; N. Fauchereau; Y. Richard; M. Rouault; C. J. C. Reason (Climate Dynamics, 2009)

Recurrent daily OLR patterns in the Southern Africa/Southwest Indian Ocean region, implications for South African rainfall and teleconnections - Nicolas Fauchereau; B. Pohl; C. J. C. Reason; M. Rouault; Y. Richard (Climate Dynamics, 2009)

The Effect of Tributyltin-Oxide on Earthworms, Springtails, and Plants in Artificial and Natural Soils - J. Römbke; S. Jänsch; T. Junker; B. Pohl; A. Scheffczyk; H.-J. Schallnaß (Archives of Environmental Contamination and Toxicology, 2007)

Ex-situ conservation of Black poplar in Europe: genetic diversity in nine gene bank collections and their value for nature development - V. Storme; A. Vanden Broeck; B. Ivens; D. Halfmaerten; J. Van Slycken; S. Castiglione; F. Grassi; T. Fossati; J. E. Cottrell; H. E. Tabbener; F. Lefèvre; C. Saintagne; et al. (Theoretical and Applied Genetics, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)